(untitled) (Revista de Biología Marina y Oceanografía, 2018)
Records of mortality after a high temperature event in 2014 in the white gorgonian Eunicella singularis were compiled in six different locations around the Chafarinas Islands. Quadrats were used to quantify dead colonies, colonies affected by epibionts and healthy colonies at different depths. No relationship was found between depth and percentage of affected colonies; however differences in the mortality among sites were detected. On average, 43% of the colonies of E. singularis were found dead, 21% damaged and 36% healthy. These results highlight the need of further researches for monitoring the colonies of this species considering future scenarios of rising temperature.